Stellar evolution confronts axion models. Issue 2 (1st February 2022) - Di Luzio, Luca; Fedele, Marco; Giannotti, Maurizio; Mescia, Federico; Nardi, Enrico
Abstract: Axion production from astrophysical bodies is a topic in continuous development, because of theoretical progress in the estimate of stellar emission rates and, especially, because of improved stellar observations. We carry out a comprehensive analysis of the most informative astrophysics data, revisiting the bounds on axion couplings to photons, nucleons and electrons, and reassessing the significance of various hints of anomalous stellar energy losses. We confront the performance of various theoretical constructions in accounting for these hints, while complying with the observational limits on axion couplings. We identify the most favorable models, and the regions in the mass/couplings parameter space which are preferred by the global fit. Finally, we scrutinize the discovery potential for such models at upcoming helioscopes, namely IAXO and its scaled versions.